1988
DOI: 10.1021/bi00421a002
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis and high-resolution NMR spectroscopy of the active site of porphobilinogen deaminase

Abstract: The active site of porphobilinogen (PBG)1 deaminase (EC 4.3.1.8) from Escherichia coli has been found to contain an unusual dipyrromethane derived from four molecules of 5-aminolevulinic acid (ALA) covalently linked to Cys-224, one of the two cysteine residues conserved in E. coli and human deaminase. By use of a hemA- strain of E. coli the enzyme was enriched from [5-13C]ALA and examined by 1H-detected multiple quantum coherence spectroscopy, which revealed all of the salient features of a dipyrromethane comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…A model built in this way may mimic one of the conformational states of the ES 2 intermediate which is formed during elongation of the polypyrrole chain. Interestingly, this intermediate has been shown to be more stable than either of the other isolable intermediates ES 1 or ES 3 (Scott et al, 1988;Warren & Jordan, 1988), suggesting that the enzyme active site can accommodate a covalently bound linear tetrapyrrole particularly favourably. This is expected since the cofactorassembly process involves the binding of the tetrapyrrole preuroporphyrinogen (S 4 ) to the apoenzyme (Awan et al, 1997).…”
Section: Modelling a Polypyrrole Intermediate In The Active Sitementioning
confidence: 96%
See 1 more Smart Citation
“…A model built in this way may mimic one of the conformational states of the ES 2 intermediate which is formed during elongation of the polypyrrole chain. Interestingly, this intermediate has been shown to be more stable than either of the other isolable intermediates ES 1 or ES 3 (Scott et al, 1988;Warren & Jordan, 1988), suggesting that the enzyme active site can accommodate a covalently bound linear tetrapyrrole particularly favourably. This is expected since the cofactorassembly process involves the binding of the tetrapyrrole preuroporphyrinogen (S 4 ) to the apoenzyme (Awan et al, 1997).…”
Section: Modelling a Polypyrrole Intermediate In The Active Sitementioning
confidence: 96%
“…NMR, isotopic labelling and mass-spectrometric studies of the Escherichia coli PBGD enzyme showed that it possesses a dipyrromethane cofactor (Fig. 2) which is covalently bound to the enzyme by a thioether linkage involving an invariant cysteine residue (Cys242 in E. coli numbering; Jordan & Warren, 1987;Warren & Jordan, 1988;Scott et al, 1988). Whilst the apoenzyme possesses no catalytic activity, incubation with PBG for a period of several hours at pH 8.0 generates active holoenzyme (Scott et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A representative example is the replacement of Cys-242 by Ser ([Ser242]HMBS). The resulting mutant enzyme lacks the anchor to which the dipyrrin cofactor has to be attached and indeed shows no activity [31]. Other deleterious replacements include the one of arginine residues at positions 11, 131, 132, and 155 by leucine or histidine, but in these cases, the mechanistic reasons are not well understood yet.…”
Section: Kinetics Of Mutant Hmbs Variants General Considerationsmentioning
confidence: 99%
“…Deaminases are unique in that they all utilize a dipyrromethane cofactor as a primer to which the four substrate molecules are covalently attached (Jordan and Warren, 1987;Hart et al, 1987;Warren and Jordan, 1988). The dipyrromethane cofactor is covalently attached to Cys-242 in the Escherichia coli deaminase sequence (Jordan et al, 1988a;Miller et al, 1988;Scott et al, 1988).…”
Section: Introductionmentioning
confidence: 99%